Innovations in Stem Cell Transplantation - Demirer, Taner (IntechOpen, 2013)
This book documents the increased number of stem cell related research, basic and clinical applications as well as views for the future. The book covers a wide range of issues related to new developments and innovations in cell-based therapies containing basic and clinical chapters from the respected authors involved in stem cell studies and research around the world. It thereby complements and extends the basic coverage of stem cells such as immunogenetics, neuron replacement therapy, cover hematopoietic stem cells, issues related to clinical problems, advanced HLA typing, alternative donor sources as well as gene therapy that employs novel methods in this field. Clearly, the treatment of various malignancies and biomedical engineering will depend heavily on stem cells, and this book is well positioned to provide comprehensive coverage of these developments.